The Influence of Renal Function Impairment on Kappa Free Light Chains in Cerebrospinal Fluid. (16th November 2021) - Konen, Franz F; Schwenkenbecher, Philipp; Wurster, Ulrich; Jendretzky, Konstantin F; Möhn, Nora; Gingele, Stefan; Sühs, Kurt-Wolfram; Hannich, Malte J; Grothe, Matthias; Witte, Torsten; Stangel, Martin; Süße, Marie; et al.
Background: The determination of kappa free light chains (KFLC) in cerebrospinal fluid (CSF) is an upcoming biomarker for the detection of an intrathecal immunoglobulin synthesis. Since renal function impairment leads to altered serum KFLC and albumin concentrations, interpretation of KFLC in CSF may be influenced by these parameters. Methods: In this two-center study, the influence of renal function (according to the CKD-EPI creatinine equation) on KFLC and albumin concentrations was investigated in patients with "physiological" (n = 139), "non-inflammatory" (n = 146), and "inflammatory" (n = 172) CSF profiles in respect to the KFLC index and the evaluation in quotient diagrams in reference to the hyperbolic reference range (KFLC IF). Results: All sample groups displayed declining KFLC indices and KFLC IF values with decreasing renal function ( P -values between <.0001 and .0209). In "inflammatory" CSF profile samples, 15% of the patients presented a KFLC index <5.9 while 10% showed an intrathecal KFLC fraction below QKappa (lim), suggesting possible false negative KFLC results. Conclusions: The influence of renal function should be considered while interpreting KFLC results in patients with neuroinflammatory diseases. The interpretation of KFLC in quotient diagrams is less susceptible to renal function impairment than the KFLC index and should be preferentially used.